Modes and rates of selfing and associated inbreeding depression in the self-incompatible plant Senecio squalidus (Asteraceae): a successful colonizing species in the British Isles. - Brennan, A; Harris, S; Hiscock, S (2005)
The strength of the self-incompatibility (SI) response in Senecio squalidus was measured across its British range. Geographic variation in SI was investigated and the extent and inheritance of pseudo-self-compatibility (PSC) and inbreeding depression were determined. Mean self-fruit-set per capitulum was calculated for individuals and sample populations. The heritability of PSC and the magnitude of inbreeding depression were assessed by comparing selfing rates and fitness trait values between SI and PSC parent-progeny lines. SI was found to be strongly expressed in S. squalidus throughout its British range, with only 3.1% of the individuals sampled showing PSC. This PSC had relatively low heritability with stronger expression of SI in selfed progeny relative to PSC parents. Inbreeding depression was shown to be great in S. squalidus, with mean life history stage values ranging from 0.18 to 0.25. The strength of SI in S. squalidus appears not to have weakened in response to its rapid colonization of Britain. The avoidance of inbreeding depression is likely to be the primary factor maintaining strong SI in this successful colonizing species.